Does Five-Factor Model Perform Better Than Three Factor Model? Evidence from Developed Countries of The Asia Pacific Region - Akbar, Ume Salma; Bhutto, Niaz Ahmed; Rajput, Suresh Kumar Oad (iRASD Journal of Economics, 2021)
This study evaluates whether the “Fama-French five-factor model” can explain the variations in expected returns better than the “three-factor model.” Using the stock returns and accounting variable data from DataStream for 1,300 plus listed firms across six developed countries of the Asia Pacific region, including; Australia, Hong Kong, Japan, Israel, New Zealand, and Singapore for the period of Jun-2006 to February-2020. The paper is the first to examine the “five-factor model” performance across the developed countries of the Asia Pacific region. The empirical findings reveal that the Asia Pacific region for the sample period earns an equity premium. In addition, results report the redundancy of size factor (SMB) and value factor (HML), while the profitability (RMW) and investment premium (CMA) are positive and significant. Moreover, the study used Gibbons, Ross, and Shanken (GRS) test to the asset pricing model. The GRS test results on the “five-factor model” compared with the “three-factor model” demonstrate that profitability and investment factors add significant explanatory power to the analysis in the Asia Pacific region.